Positive and Negative Themes Depicted in Combat-Related Sports Films - Andrew Watts BS; Christy Lucas BS; Eric Brzozowski MD; Zachary Winthrop MD; Tonya S. King PhD; Robert P. Olympia MD (SAGE Publishing, 2019)
Participation in boxing, mixed martial arts, and wrestling is extremely popular among children and adolescents. The objective of this study was to determine themes depicted in a select number of combat-related films. Twenty films were independently viewed and analyzed by 4 reviewers. The average number of positive and negative themes was 34.4 and 18.1 mean events/hour for all included films, respectively. The most common positive themes were "positive interactions with family/friends/fans," "importance of mentorship," and "positive interactions with a coach/trainer" (4.23, 3.63, and 3.06 mean events/hour, respectively). The most common negative themes were "choosing to do the wrong thing," "negative interactions with family/friends/fans," and "poor sportsmanship" (2.70, 2.00, and 1.58 mean events/hour, respectively). In conclusion, the co-viewing of combat-related films among pediatric athletes and their coaches/trainers and/or parents in order to focus on "teachable moments" may encourage the acquisition and development of positive themes and the avoidance and de-emphasis of negative themes.